THE SOCIAL STRATIFICATION ON SUKU LAUT FISHERMEN IN BERAKIT VILLAGE OF TELUK SEBONG DISTRICT OF BINTAN REGENCY OF RIAU ISLAND PROVINCE - Wanti Hotnida Tarihoran; Ridar Hendri; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in May 2017 on “Suku Laut” fishermen in Berakit village, Teluk Sebong district of Bintan regency of Riau Island Province. The purpose of this research is: to identify social, culture and economic condition of Suku Laut, to know the cause and process of soial stratification of Suku Laut fisherman( in the aspect of power, privilege/previlese and prestige/prestise). The method used is non-participant observation method. The determination of respondents used is cencus technique to 30 families. Data analysis used is qualitative analysis.The result showed that: first, social condition (kinship of Suku Laut still high; relationship with the community in Berakit village remained good); culture condition (culture values are still preserved, among others: Keduri events, playing musical instruments dan dances during traditional events); economic condition (education becomes mandatory right now, income level is divided into 3 groups is groups with revenues of more than 1 million, 1 million up to 1,5 million dan less than 1 million). Second,factors that cause of statification in the aspect of power are wealth and education; aspects of previlese (previlege) namely science and the line of stature; aspects of prestige (prestise) is a good position and word. Third, social stratification prosess in society does not result in social gaps (Suku Laut still help each other and communicate with each other). Keywords: Social Stratification, Suku Laut, Bintan, Panglong